Pengaruh Pelatihan, Pengembangan SDM, dan Budaya Organisasi terhadap Kompetensi Gen Z - Widodo, Bima Prawira; Hariyadi, Guruh Taufan; Sartika, Mila; Perdana, Tito Aditya (Universitas Islam Kadiri, 2025)
This study aims to examine the influence of training, human resource development, and organizational culture on enhancing the competencies of Generation Z employees at Bimbi Toys and Accessories. While training and HR development are considered essential to strengthening competencies, organizations often face challenges in tailoring programs to the adaptive and innovative characteristics of Generation Z. The research employs a quantitative descriptive-analytical approach with a sample of 100 respondents. Data were collected through questionnaires and analyzed using SmartPLS 3.0 software to evaluate the relationships among variables. The findings reveal that the three exogenous variables Training, HR Development, and Organizational Culture are valid and reliable constructs of measurement and have a positive and significant effect on the competencies of Generation Z employees. These results highlight the importance of integrating organizational culture with training and HR development programs to foster adaptive and innovative employee competencies, particularly in addressing the distinct characteristics of Generation Z in the workplace.